PERAN MAHASISWA DALAM MENUMBUHKAN SIKAP BELA NEGARA DI KALANGAN MASYARAKAT - Enjelina Feronika Pakpahan; Ira Lasmaida Nadeak; Chelsy Situmorang; Siti halima Ompusunggu; Winda hutabalian (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to understand the meaning of defending the country, analyze the attitude of defending the country among society today, and identify the role of students in fostering an attitude of defending the country among society. This research uses descriptive qualitative methods with data collection techniques through interviews with 5 students from various study programs at HKBP Nommensen University Pematangsiantar. The research results show that defending the country is the attitude and actions of every citizen to defend the sovereignty of the country, territorial integrity and the values ​​of Pancasila. The attitude of defending the country among society currently still needs to be improved, with various challenges faced such as a lack of understanding about defending the country, community apathy, and a low sense of unity and oneness. Students have an important role in raising awareness of national defense in society through various efforts, such as being role models in behavior, carrying out educational and outreach activities, and utilizing technology to defend the country.